2023
DOI: 10.1037/dhe0000364
|View full text |Cite
|
Sign up to set email alerts
|

The link between high-impact practices and college success among international students in the U.S.

Abstract: To promote learning and academic success among undergraduates, many colleges and universities offer or require students to participate in high-impact practices, which include first-year seminars, learning communities, writing-intensive courses, service-learning, diversity/global learning, internships, and capstone projects. However, the research findings on the effectiveness of these practices for promoting academic achievement and retention is mixed. Moreover, few studies have examined the link between these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…A growing body of research suggest that these factors influence an array of outcomes among both White students and students of color, including their college adjustment, engagement, motivation, self‐efficacy, sense of belonging, and eventual success (Castro Samayoa, 2018; Druery & Brooms, 2019; Muñoz & Espino, 2017; Museus, 2008; Museus & Chang, 2020; Museus et al., 2019). Despite these advances, with few exceptions (Katsumoto & Bowman, 2021), research that centers these marginalized voices and the frameworks they inform have largely been minimized, if not ignored, in HIPs discourse.…”
Section: Disconnect Between Hips and Knowledge From The Marginsmentioning
confidence: 99%
“…A growing body of research suggest that these factors influence an array of outcomes among both White students and students of color, including their college adjustment, engagement, motivation, self‐efficacy, sense of belonging, and eventual success (Castro Samayoa, 2018; Druery & Brooms, 2019; Muñoz & Espino, 2017; Museus, 2008; Museus & Chang, 2020; Museus et al., 2019). Despite these advances, with few exceptions (Katsumoto & Bowman, 2021), research that centers these marginalized voices and the frameworks they inform have largely been minimized, if not ignored, in HIPs discourse.…”
Section: Disconnect Between Hips and Knowledge From The Marginsmentioning
confidence: 99%
“…While both SA from U.S. universities and IaH have been examined intensively as explained above, the target beneficiaries of those practices have been predominantly domestic students. Some scholars have examined the potential benefits of general experiences on international students (e.g., high impact practices, Katsumoto & Bowman, 2021), studied international students’ unique barriers to engaging in learning (e.g., linguistic barriers, Yao, 2016), or compared psychosocial outcomes of international students with domestic students (e.g., mental health, Liu et al 2019). However, in contrast to the growing attention paid to such general experiences of international students, scholars have barely examined whether international education offered by a host country can be meaningful for international students.…”
Section: Literature Reviewmentioning
confidence: 99%
“…An unpublished dissertation found that learning communities were positively linked with retention at community colleges (Wurtz, 2014, cited in Katsumoto & Bowman, 2021. Katsumoto and Bowman (2021) in their study on international student success, found that participation in learning communities was one of the few HIP experiences that positively impacted international students' GPA, sense of belonging, and college satisfaction, which they attributed to the "collectivistic environment" in learning communities.…”
Section: Overview Of the Literature On Learning Communitiesmentioning
confidence: 99%